2020
DOI: 10.3846/mma.2020.11112
|View full text |Cite
|
Sign up to set email alerts
|

Application of Higher Order Haar Wavelet Method for Solving Nonlinear Evolution Equations

Abstract: The recently introduced higher order Haar wavelet method is treated for solving evolution equations. The wave equation, the Burgers’ equations and the Korteweg-de Vries equation are considered as model problems. The detailed analysis of the accuracy of the Haar wavelet method and the higher order Haar wavelet method is performed. The obtained results are validated against the exact solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 69 publications
2
6
0
Order By: Relevance
“…The obtained results will be validated by a number of case studies by computing the numerical rates of convergence and comparing the obtained and theoretical results. These results are confirmed in [47][48][49][50][51][52][53] and in other papers.…”
Section: Theorem Let Us Assume Thatsupporting
confidence: 86%
See 1 more Smart Citation
“…The obtained results will be validated by a number of case studies by computing the numerical rates of convergence and comparing the obtained and theoretical results. These results are confirmed in [47][48][49][50][51][52][53] and in other papers.…”
Section: Theorem Let Us Assume Thatsupporting
confidence: 86%
“…The convergence rate of the method was improved from 2 to 2 + 2 s, where s stands for the method parameter. This new method is currently underused, but the first results obtained have shown that a principal growth of the accuracy can be achieved with a minimum growth of complexity [51][52][53]. In [52], the free vibrations analysis of the Euler-Bernoulli nanobeam was performed.…”
Section: Introductionmentioning
confidence: 99%
“…The time moment t f = max(0.5, t c ) was determined by obtaining the value of critical time moment t c which is the maximal time t for which max x,t<tc |u(x, t) − u e (x, t)| < 10 −3 . These numerical results were compared with the uniform grid results previously published in [76]. Such numerical results are shown in Table 2.…”
Section: Discussion Of Numerical Resultsmentioning
confidence: 95%
“…The KdV equation (4.3) was solved at various resolutions J and the numerical results were compared to the exact solution (4.4). The uniform grid results from [76] were used and new results with the nonuniform grid (2.3) and the adaptive grid (2.4) were calculated. The numerical result itself was used as the basis for the weight function in the adaptive grid for this model equation.…”
Section: Discussion Of Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation